Hubungan Antara Kecerdasan Spiritual dengan Regulasi Emosi pada Narapidana Kelas IIA Sumbawa Besar - Mulya Putri Amanatullah; Ayuning Atmasari; Lukmanul Hakim (JURNAL PSIMAWA, 2020)
Spiritual intelligence is the ability of a person to deal with and solve problems of meaning and value which are closely related to one's emotions. This study aims to determine the relationship between Spiritual Intelligence and Emotional Regulation in Class IIA Prisoners Sumbawa Besar. This study uses a quantitative descriptive approach. Simple Random Sampling was used as the research sampling technique. Slovin formula was used in the withdrawal of samples. The research sample was 81 class IIA prisoners at Sumbawa Besar. The research data were obtained using research instruments in the form of spiritual intelligence scale and emotional regulation. The results of this study indicate that there is a relationship (correlation) between spiritual intelligence and emotional regulation with a correlation coefficient of 0.444 with a calculated p value of 0.0001 / p <0.05, which means that the higher the spiritual intelligence, the higher the emotional regulation of the prisoners, and vice versa, the lower the spiritual intelligence, the lower the emotional regulation of the prisoners. The results also showed that prisoners' spiritual intelligence in general was in the moderate category of 39% and emotional regulation also showed that they were generally included in the moderate category of 31.7%.